2017
DOI: 10.1016/j.cjtee.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Shahid Rajaee hospital administrative data on injuries resulting from car accidents in Shiraz, Iran: 2011–2014 data

Abstract: PurposeThe administrative data from trauma centers could serve as potential sources of invaluable information while studying epidemiologic features of car accidents. In this cross-sectional analysis of Shahid Rajaee hospital administrative data, we aimed to evaluate patients injured in car accidents in terms of age, gender, injury severity, injured body regions and hospitalization outcome in the recent four years (2011–2014).MethodsThe hospital registry was accessed at Shiraz Trauma Research Center (Shiraz, Ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…The risk of road traffic mortality increased with age. The result matches the findings from several studies [30][31][32][33][34]. This result may be explained by the deterioration in health with aging.…”
Section: Discussionsupporting
confidence: 91%
“…The risk of road traffic mortality increased with age. The result matches the findings from several studies [30][31][32][33][34]. This result may be explained by the deterioration in health with aging.…”
Section: Discussionsupporting
confidence: 91%
“…Legislation on seatbelt, helmet and child restraint use needs to be improved in China. The sex ratio of patients sustaining transport accidents was 1.61:1, which is lower than the ratios reported in Iran (2.2:1) and Romania (2.0:1) [9,37]. This difference may be explained by the more active participation of Chinese women in driving-related and outdoor activities than women in the other countries.…”
Section: Discussionmentioning
confidence: 58%
“…Studies of nonfatal UIs are an important part of the overall picture of UIs [6,7]. Although much is known about fatal injuries via the vital registry system, there are limited data on nonfatal injuries in LMICs, with most information being based on questionnaire surveys and trauma registries or focused on a select group of injuries or population [8][9][10][11][12]. Although the National Injury Surveillance System (NISS) was built in China since 2006, it includes only 126 hospitals with limited representation and collects information using hard-copy forms, which leads to poor availability of real-time data [13].…”
Section: Introductionmentioning
confidence: 99%
“…The results of their research revealed that among 30 provinces of Iran, 12 were developed, nine were semi-developed, and nine were underdeveloped, in their categorization, Kermanshah Province was among the semi-developed provinces [33]. Studies conducted in Kermanshah the high significant rates for HIV/AIDS [34], cancer [35], cardiovascular diseases [36], accidents [37], high total fertility rates [38], and inadequate access to health centers [11].such evidences revealed the need for assessing healthcare resources and surviving the access to these cares. Since increasing the level of health and easy access to medical care are among the most prominent needs in development plans and considering the fact that the Kermanshah Province is one of the deprived provinces of Iran and given the prevalence of the above mentioned challenges in Kermanshah, this paper aimed to investigate the inequality in access to medical care in the townships based in Kermanshah, Iran according to population density.…”
Section: Introductionmentioning
confidence: 99%